2016
DOI: 10.7752/jpes.2016.03137
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Abstract:Relevance of the work associated with the need to develop special methods of teaching motor actions in climbing primary school children. The purpose of research -theoretical and experimental methodology to justify the construction of training process of young climbers 6-7 years at the initial stage of preparation. The study involved 42 children 6-7 years of age who are engaged in sports climbing club "Ant"; and the experimental and the control group consisted of twenty-one competitor, out of which 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 9 publications
3
8
0
7
Order By: Relevance
“…However, such method of control is not always acceptable. That is why it is recommended to supplement heart beats rate indicators by indicators of load tension's subjective assessment [Borg, 1982;Kozina et al, 2016aKozina et al, , 2016b. That is why it is not good to underestimate human potentials to regulate load's intensity, basing on subjective feelings.…”
Section: Discussionmentioning
confidence: 99%
“…However, such method of control is not always acceptable. That is why it is recommended to supplement heart beats rate indicators by indicators of load tension's subjective assessment [Borg, 1982;Kozina et al, 2016aKozina et al, , 2016b. That is why it is not good to underestimate human potentials to regulate load's intensity, basing on subjective feelings.…”
Section: Discussionmentioning
confidence: 99%
“…It was revealed that in the experimental group the indicators of the tests " push-ups 30 s ", "Romberg's test", "jumping with a ring in the hands of 2x5 m", "dribbling through the chips in Постановка проблеми. Заняття з дітьми 5-6 років, які відвідують заняття з футболу, повинні будуватися з урахуванням показників функціональних можливостей дитячого організму, які є провідними критеріями в спорті при виборі фізичних навантажень, структури рухових дій, методів впливу на організм [7,8,11,12]. У зміст таких занять рекомендується широко включати рухливі ігри, елементи різних спортивних ігор та інших доступних їм фізичних вправ.…”
Section: The Development Of Physical Qualities Using the Game Methods In The Training Process Ofunclassified
“…Якщо футболіст пробігав з м'ячем між двох фішок, колір яких був не однаковий, це не зараховувалося. Фіксувалася кількість фішок, які пройшов спортсмен за 1 хвилину [5,7].…”
Section: The Development Of Physical Qualities Using the Game Methods In The Training Process Ofunclassified
“…In this study, methods were used to determine the psychophysiological abilities in terms of time indicators of a simple and complex reaction. Tests were conducted on the computer program "Psychodiagnostics" (Kozina et al, 2016).…”
Section: Methods Of Psychophysiological Testingmentioning
confidence: 99%